He, She, They? The Impact of Gendered Language on Economic Behavior - Paul M. Gorny; Petra Nieken; Karoline Ströhlein (Center for Economic Studies and ifo Institute (CESifo), 2023)
We conducted a controlled experiment to study how different gender frames used in the instructions affect economic behavior. In our experiment, we systematically varied the framing of the instructions, either using the male, the female, or a gender-inclusive form. Participants played three standard economic two-player games measuring prosocial behavior. In particular, we elicited the degree of sharing, reciprocal behavior, and honest reporting. We investigated if participants behaved differently if their self-reported gender matched the grammatical gender used in the instructions. The results reveal that the framing of instructions had the strongest impact on sharing, and the effects were mainly driven by participants self-identifying as men. In contrast, we observe only mild treatment differences, if any, regarding reciprocal behavior or honest reporting. We discuss the potential mechanisms and consequences of our findings.
Keywords: C91; D01; J16; Z13; 330; gender; gender inequality; gender stereotypes; grammatical gender; language; experimental methodology